Influence of Natural Polymers on Zolmitriptan Oral Fast Dissolving Film Formulations: A New Approach to Migraine Treatment - Talamanchi, Balakrishna; Javvaji, Venkateswara Rao; Dogiparthi, Lakshman Kumar; Sajja, Jayanth Babu; Nimmagadda, Sai Sruthi; Parasa, Vijaya Preethi; Tadikonda, Pavan Ramakrishna; Shaik, Sabreen; Shaik, Fahamida; Shaik, Raheema (International Journal of Pharmaceutical Investigation, 2026)
Introduction The main purpose of zolmitriptan fast-dissolving films aims to deliver zolmitriptan effectively alongside quick action for migraine therapy through a user-friendly dosage method. Fast dissolving films dissolve rapidly in the mouth through a waterless process to offer convenient treatment to people with swallowing problems along with patients enduring nausea or vomiting while experiencing migraine attacks. Materials and Methods Zolmitriptan oral films with fast dissolution capability were formulated through a combination of Gum Karaya and Gum Olibanum as natural film-forming agents. Glycerin acted as a plasticizer together with the stabilizing agents which included citric acid and stevia powder. Production of these films occurred through the solvent casting technique. Results and Discussion Researchers developed Zolmitriptan fast-dissolving films through oral administration which received evaluation regarding weight consistency and drug content along with film thickness and folding strength evaluation. The experimental findings matched the required values. The Franz diffusion cell apparatus served to conduct in vitro diffusion tests that utilized 6.8 pH phosphate buffer as the dissolution solution Zolmitriptan fast-dissolving films containing Gum Karaya and Gum Olibanum the drug release reached 98.99% in 5 min. The combination of Gum Karaya and Gum Olibanum improved film features by increasing solubility and dissolution rate and tensile strength beyond individual use of each gum. The pure drug and optimized formulation product Z7 showed transparent spectra through FTIR investigation which proved that the drug material did not interact with the optimized formulation. DSC analysis of pure drug with Gum Karaya and Gum Olibanum and optimized formulation (Z7) showed no physical changes or chemical degradation of drug substance or polymers or formulation components during testing. This proved overall stability of the optimized formulation.
Keywords: Zolmitriptan; Oral fast dissolving films; Solvent casting method; Polymers and plasticizers